Career networking 3.0 - UiTMLaw maintains strong relations with industry giants - UiTM, Faculty of Law (Faculty of Law, 2022)
On 20 August 2022, UiTMLaw once again organised the UiTM Law: Virtual Career Networking 3.0, one of the faculty's initiatives to link the graduating students with the legal industry and accord them a once in a lifetime opportunity to engage renowned law firms, corporations and the Malaysian Judiciary in the step of their career planning process. The unwavering support shown by the legal industry made a remarkable difference in charting the future of UiTMLaw participating graduating students, who have been given the golden opportunity of one•on-one sessions with prospective employers from the giants of the legal industry in Malaysia. As such, no words can express UiTMLaw's gratitude to the Malaysian Judiciary, the Attorney General's Chambers of Malaysia, Petronas. Maybank, Messrs Azmi & Associates, Messrs K K Lim, Messrs Thomas Philip, Messr Raja, Darryl & Loh, Messrs Rahman Rohaida, Messrs Rosli Dahlan Saravana Partnership, Messrs Lee Hishamuddin Allen & Gledhill, Messrs Azhar Aziz & Associates and Messrs Shook Lin & Bok, for spending time with the graduating students as they present their pitches.